Rational design of interface refining through Ti4+/Zr4+ diffusion/doping and TiO2/ZrO2 surface crowning of ZnFe2O4 nanocorals for photoelectrochemical water splitting. Issue 9 (19th March 2021) - Kim, Sarang; Mahadik, Mahadeo A.; Periyasamy, Anushkkaran; Chae, Weon-Sik; Ryu, Jungho; Choi, Sun Hee; Jang, Jum Suk
Abstract : The interplay between diffusion/doping and surface passivation of TZF NCs exhibits a breakthrough photocurrent density of 0.73 mA cm −2 (1.23 V vs. RHE) with 98% stability over 10 h in the TZF/Al2 O3 /CoO x photoanode. Abstract : The development of advanced assemblies of interfacial under- and overlayered photoanodes is an effective technique to overcome the problem of slow charge separation and enhance solar energy conversion. The present study reports in situ zirconium-doped zinc ferrite nanocorals (Zr-ZFO NCs) and introduces the concept of diffusion/doping and surface passivation using a TiO2 underlayer via quenching. The high-temperature quenching aids the Zr doping/Ti 4+ diffusion in the bulk and, at the same time, the ZrO2 /TiO2 composite layers passivate the surface of ZFO NC photoanodes. The optimum TiO2 -underlayer-modified Zr-ZFO (TZF) photoanode shows a dramatically improved photocurrent (0.48 mA cm −2 ) at 1.23 V vs. RHE, which is twice that of the bare Zr-ZFO. Further, the addition of an Al2 O3 /CoO x cocatalyst further accelerates the surface reaction kinetics of the TZF, and significantly improved charge separation efficiency, photocurrent density (0.73 mA cm −2 at 1.23 V vs. RHE; and 0.97 mA cm −2 at 1.4 V vs. RHE), and stability were obtained. Compared to conventional ZFO nanorods (0.14 mA cm −2 at 1.23 V vs. RHE), the optimized sample shows a 421% increase in photocurrent density. Additionally, the TZF/Al2 O3 /CoO x _1 mM photoanode generates 65 and 130 μmol oxygen and hydrogen, respectively, under simulated 1 sun illumination. Thus, the "sandwich" strategy for Zr-ZFO with a TiO2 underlayer and spontaneous surface passivation via quenching could be expanded for the design and fabrication of many low-efficiency photocatalysts and the production of cost-effective PEC water splitting photoelectrodes.